DEVELOPMENT AND CHARACTERIZATION OF HYDROXYL CHLOROQUINE SULPHATE (HCQ) NANOPARTICLES (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The objective of present study was to formulate and characterize the nanoparticles of hydroxyl chloroquine sulphate (HCQ). Nanoparticles were prepared by the w/o/w emulsion - solvent evaporation method using polymer Eudragit® RL-100, acetone, and surfactant poloxmer-188 solutions. Amount of polymer, organic solvent and surfactant was selected as formulation variable. Characterization of the nanoparticles was performed by measuring particle size, zeta potential, surface morphology, interactions, drug entrapment efficiency, in-vitro drug release, % yield and stability. The formulated nanoparticles were found to be spherical and uniform in particle size with less than one poly dispersity index. The zeta potential of nanoparticles was found -34 (mv) represent higher stability of colloidal dispersion. In another set of characterization the percentage yield and entrapment was found to be in the range of 55-68% and 63.14% respectively. The in-vitro release shows 87.93% at its maximum level in 24 hours of study. The suspension of formulation was found more stable in refrigerated environment. The release kinetics evaluation revealed the drug release was following Higuchi model, which ensures the possibility of long term release profile from the nanoparticles formulation so that its concentration maintained within therapeutic level for larger period of time so that safe and efficacious for malarial and rheumatoid patients.